2021
DOI: 10.1039/d1ce00253h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motion of halogenated ethylammonium/[18]crown-6 supramolecular ions in nickel dithiolate magnetic crystals

Abstract: Supramolecular cations, consisting of ethylammonium derivatives (X-CH2CH2-NH3+) complexed with [18]crown-6, were incorporated into [Ni(dmit)2]– crystals in order to promote molecular motion. Crystals of (X-CH2CH2-NH3+)([18]crown-6)[Ni(dmit)2]– (1: X=H, 2: X=F, 3: X=Cl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…In our recently reported analogues, which adopt dibenzyl-18-crown-6 and benzo-18-crown-6, similar motion-induced NTE was observed, and both displayed the tendency that NTE effect becomes similar at low temperatures. In particular, (F–C 2 H 4 NH 3 )­(18C6)­[Ni­(dmit) 2 ], whose 18C6 was ordered at each measured temperature, simply displayed linear anisotropic thermal expansion (Figure S8a), while (Cl–C 2 H 4 NH 3 )­(18C6)­[Ni­(dmit) 2 ], along with the rotation of 18C6, displayed a small change in thermal expansion coefficient when such rotation was frozen (Figure S8b).…”
Section: Resultsmentioning
confidence: 99%
“…In our recently reported analogues, which adopt dibenzyl-18-crown-6 and benzo-18-crown-6, similar motion-induced NTE was observed, and both displayed the tendency that NTE effect becomes similar at low temperatures. In particular, (F–C 2 H 4 NH 3 )­(18C6)­[Ni­(dmit) 2 ], whose 18C6 was ordered at each measured temperature, simply displayed linear anisotropic thermal expansion (Figure S8a), while (Cl–C 2 H 4 NH 3 )­(18C6)­[Ni­(dmit) 2 ], along with the rotation of 18C6, displayed a small change in thermal expansion coefficient when such rotation was frozen (Figure S8b).…”
Section: Resultsmentioning
confidence: 99%
“…30 The comparable activation energy observed in crystal 1 indicates the suitable spatial environment for the [18]crown-6 rotation in the crystalline state. 26,31–35…”
Section: Resultsmentioning
confidence: 99%
“…30 The comparable activation energy observed in crystal 1 indicates the suitable spatial environment for the [18]crown-6 rotation in the crystalline state. 26,[31][32][33][34][35] The temperature dependence of the molar magnetic susceptibility (χ m ) and the magnetisation curves are shown in Fig. 4.…”
Section: †)mentioning
confidence: 99%
“…28 In this series of 1D spin systems, the halogen substituent group in the phenyl ring of the cation has effects on the crystal structures and the magnetic transition temperature of these spin-Peierls-like complexes. Takahashi et al 40 applied the supramolecular approach to design crystals of ( In this study, we design nickel dithiolene crystals of [Et 3 N(CH 2 ) 3 X][Ni(mnt) 2 ] (1: X = H, 2: X = Cl, 3: X = Br and 4: X = I and Br) (Scheme 1), which contains triethylpropylammonium halide chains (X-CH 2 CH 2 CH 2 -NEt 3 + ). Crystal structures of 1-4 clearly showed that the halogenated alkyl chain has an effect on the arrangement of cations and anions within the crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi et al . 40 applied the supramolecular approach to design crystals of (X–CH 2 –CH 2 –NH 3 + )([18]crown-6)[Ni(dmit) 2 ] − , which contain alkylammonium halide chains (X–CH 2 –CH 2 –NH 3 + ) (X = H, F, Cl, and Br). The halogenated alkyl chains in (X–CH 2 –CH 2 –NH 3 + )([18]crown-6)[Ni(dmit) 2 ] − display motional freedom within the crystals; especially, Br–CH 2 CH 2 –NH 3 + exhibits dynamic disorder between four sites, and the morphology and size of supramolecular cations have significant effects on the arrangement and magnetic behavior of [Ni(dmit) 2 ] − .…”
Section: Introductionmentioning
confidence: 99%